269 Influence of the maternal rumen microbiome on development of the calf meconium and rumen microbiome. (30th November 2020) - Woodruff, Kelly; Hummel, Gwendolynn; Austin, Kathleen; Smith, Travis; Cunningham, Hannah
Abstract: Optimization of host performance may be achieved through programming of the rumen microbiome. Thus, understanding maternal influences on the development of the calf rumen microbiome is critical. We hypothesized that the cow maternal rumen microbiome would influence colonization of the calf rumen microbiome. Our objective was to relate the microbiome of the cow rumen fluid prior to parturition (RFC) and at weaning (RFCw) to the calf's meconium microbiome (M) and calf rumen fluid microbiome at birth (RFd1), d 2 (RFd2), d 28 (RFd28), and weaning (RFNw). Multiparous Angus crossbred cows (n = 10) from the University of Wyoming beef herd were used. Rumen fluid was collected from the cows prior to parturition and at weaning. Immediately following parturition, meconium and rumen fluid were collected from the calf. Rumen fluid was collected again at d 2, 28, and at weaning. Microbial DNA was isolated and 16S rRNA sequencing was completed on the Illumina MiSeq. Sequence data were analyzed with QIIME2 to determine both alpha and beta diversity by sample type and day. Alpha diversity metrics reported similarities in the early gut microbiome (M, RFd1, and RFD2; q ≥ 0.12) and between the cow and calf at weaning (q ≥ 0.06). Microbial composition as determined by beta diversity differed in the early rumen microbiome (RFd1, RFd2, and RFd28; q ≤ 0.04). There were similarities in composition between M, RFCw, and RFd1 (q ≥ 0.09). These data can be used to develop hypotheses for the pathway of colonization in the early gut and can provide insight into management practices affecting the microbiome, improving host performance.